2010
DOI: 10.1111/j.1745-4557.2010.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

DESCRIPTIVE STUDY OF REFLECTANCE SPECTRA OF HAKE (MERLUCCIUS AUSTRALIS), SALMON (SALMO SALAR) AND LIGHT AND DARK MUSCLE FROM TUNA (THUNNUS THYNNUS)

Abstract: The reflectance spectra of foods constitutes a simple, non‐destructive physical method with potential applications in the industry. Color is the most valued properties for customers when buying fresh fish, so that its characterization is important for setting objective quality criteria that can be easily applied at all levels of the production and distribution chain. In this work the reflectance spectra and CIEL*a*b* coordinates of fresh muscle in hake, salmon and tuna (light and dark muscle) it was described.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
(48 reference statements)
2
7
0
Order By: Relevance
“…Colour is considered significant properties for acceptance of fish products due to direct effect on consumer's selection (Lawless & Heymann, 2010). No any significant difference and effect on colour were reported (Özyurt et al., 2015; Sathivel, 2005) except low values of redness in hake fillet (Lopez de Lacey et al., 2014; Sánchez‐Zapata, Pérez‐Alvarez, Fernández‐López, & Barber‐Valles, 2010) which resembles our study and indicated that the colour was stable throughout the storage period in the treatments in which probiotics were used. The fish composition may influence the sensory characteristics like colour, odour and texture during storage (Abdollahi, Rezaei, & Farzi, 2014).…”
Section: Discussionsupporting
confidence: 75%
“…Colour is considered significant properties for acceptance of fish products due to direct effect on consumer's selection (Lawless & Heymann, 2010). No any significant difference and effect on colour were reported (Özyurt et al., 2015; Sathivel, 2005) except low values of redness in hake fillet (Lopez de Lacey et al., 2014; Sánchez‐Zapata, Pérez‐Alvarez, Fernández‐López, & Barber‐Valles, 2010) which resembles our study and indicated that the colour was stable throughout the storage period in the treatments in which probiotics were used. The fish composition may influence the sensory characteristics like colour, odour and texture during storage (Abdollahi, Rezaei, & Farzi, 2014).…”
Section: Discussionsupporting
confidence: 75%
“…3 shows the reflectance spectra of samples measured with the white ceramic as background and also the white ceramic reflectance spectra without sample. In some zones, the reflectance spectra of tuna pâté is similar to that of fresh tuna dark muscle (Sánchez-Zapata et al, 2010), although with higher values. Tuna pâté also showed two plateaus characteristic of fresh tuna dark muscle between 360 and 440 nm and 470e550 nm, indicating that this is the same fish species and the same type of muscle (Sánchez-Zapata & Pérez-Alvarez, 2007;Sánchez-Zapata et al, 2010).…”
Section: Reflectance Spectramentioning
confidence: 80%
“…This could be due at the high red component in tuna dark muscle (Sánchez-Zapata & Pérez-Alvarez, 2007;Sánchez-Zapata et al, 2010). Tuna is a fat fish that feeds on zooplankton, which is rich in astaxantin, a carotenoid that accumulates in the muscle of tuna, particularly in dark muscle (Ingemansson, Pettersson, & Kaufmann, 1993), while the Mb concentration in fresh tuna meat is 3e14 times higher than in animal carcasses (Kanoh et al, 1986).…”
Section: Effect Of Backgroundmentioning
confidence: 99%
See 2 more Smart Citations